استنباط قاعدة سد الذرائع من السنة وأثرها ف اإلفتاء ف القضايا املعارصة للمرأة ف بنغالديش =Deriving the principle of Sadd al-Dharāʾiʿ from the sunnah and its impact on the fatwa on contemporary issues of women in Bangladesh - Nurunnabi, Muhammad; Amanullah, Muhammad (IIUM Press, 2021)
This research aims at studying the rule of sadd al-dharāʾiʿ in terms of its application in some contemporary issues of women in Bangladesh. Amongst the most prominent of these issues is the concept of woman’s ʿawrah that has effects on all of her affairs and related rulings. In this context, the study will discuss the concept of ʿawrah and how the rule of sadd al-dharāʾiʿ is applied on it, and in some other women’s issues which has led to embarrassment, hardship and woman being deprived of exercising her fixed rights in Islamic law, which in fact equates both genders in terms of rights and duties. The study adopts inductive and analytical approaches.